Occupational exposure to respirable crystalline silica at an underground copper mine in Zambia. - Nabiwa, Lubinda; Linde, Stephanus J L; Habanyama, Adrian; Hayumbu, Patrick; Sifanu, Mwaba; Masekameni, Masilu Daniel (Annals of Work Exposures & Health, 2025)
Introduction Overexposure to respirable crystalline silica (RCS) can lead to the development of silicosis and other respiratory diseases. The mine under study was reported to have the highest number of certified cases of pneumoconiosis in Zambia in 2015, and in 2008, a study revealed that 56% of the RCS samples exceeded 0.05 mg/m3. This study aims to assess occupational exposure to RCS at this underground copper mine. Method In this cross-sectional study, personal exposure monitoring was conducted using National Institute for Occupational Safety and Health's methods 0600 and 7602 (KBr pellet), and 114 samples were collected. Gravimetric analysis of respirable dust (RD) samples and quantification of RCS were performed at an ISO 17025:2005 accredited analytical laboratory. BOHS-NVvA 2022 standard was used for determining activity areas' overexposure. Results The median, 95th percentile (P95), and maximum (Max) RD concentrations were 0.279, 1.650, and 3.7 mg/m3, respectively. For the RCS exposure, the median, P95, and Max RCS exposure concentrations were 0.02, 0.179, and 0.548 mg/m3, respectively. Thirteen (11.7%) of the 111 samples had exposure exceeding the Republic of South Africa (RSA) TWA-OEL of 0.1 mg/m3, and 11 out of 18 activity areas were statistically overexposed to RCS when applying the BOHS-NVvA 2022 standard. Discussion The number of RCS samples exceeding 0.05 mg/m3 reduced from the 67% recorded in 2008 to 32.4% in this study. One factor that could have led to this reduction is the mine not working at full capacity during the sampling period. However, the lack of adherence to the occupational health and safety (OHS) guidelines by the miners still leads to personal exposure above the limits set by various countries. Conclusion Exposure to RCS in more than half of the activity areas was not under control. Routine RCS monitoring in Zambian mines should be mandatory, as this is not an isolated case, though it is more of a challenge at this mine because of the high percentage of RCS in RD samples (18.5%). Miners should be continuously trained on the importance of adhering to the OHS guidelines. Furthermore, Zambia should consider adopting the RSA occupational exposure limit for RCS and the BOHS-NVvA 2022 standard for exposure level compliance testing.